Dispersion-driven formation of chiral twisted PAH double helices - Yang, Xuan; Brückner, Margit; Rominger, Frank; Kirschbaum, Tobias; Mastalerz, Michael (Chem, 2024)
Molecular double helices are ubiquitous in nature and have also been generated artificially. They are usually based on helical ribbons. Here, a new type of double helix based on twisted ribbons is introduced. The monomeric strands are polycyclic aromatic hydrocarbons of various lengths, with up to 25 linearly annulated six-membered rings. Single-crystal X-ray structure analysis revealed that the major driving forces in the creation of these helices are multiple dispersion interactions of alkyl substituents. The thermodynamic stability and formation of the twisted double helices were studied by NMR, while the kinetics of their inversions was studied by circular dichroism spectroscopy. In combination with theoretical calculations, the mechanism of isomerization is suggested to depend on the rate of monomerization of double-helical strands rather than the double helices racemizing themselves as intact pairs. This new type of double helix based on twisted nanoribbons, in combination with its aromatic nature, opens up new possibilities in designing chiral materials.
Online veröffentlicht am 22. Januar 2024, Version of Record online veröffentlicht am 14. März 2024
Gesehen am 25.06.2024